Implementation of PT Mulyosari Group's Leadership Style in Improving Employee Work Performance - Pryatmoko, Dimas Yovie; Majid, Nurkholish (International Journal of Asian Business and Management, 2023)
Leadership is a form of leaders' efforts to shape culture within an organization or company, the application of a good leadership style aims to prosper the members. The       results of the application of the existing leadership style in the previous period became the evaluation benchmark for the new leadership, this study aims as an effort to increase the interest of students or prospective students to participate in student organization activities amid the many volunteers and the Ministry of Education's program by showing different leadership flows, democratic leadership styles, in an organization if there is a problem, they must always discuss it with the team with the object of the COO of PT Mulyosari Group using descriptive qualitative methods with a leadership style approach